Consultation for Parent to Increase Assertive Behavior of Elementary School Student (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to examine the effect of consultation for parents on improving assertive behavior of elementary school students. This study used a pretest posttest one group design which was conducted for 5 students and 5 parents who were selected through purposive sampling. Consultation for parents to improve students' assertive behavior lasts for 2 sessions. Session 1 consists of the formation stage, problem exploration, setting goals, identifying consultative situations and planning consultations by consultants. While in the second session evaluation and follow-up were carried out. Data analysis in this study used Wilcoxon nonparametric analysis. From the analysis of Wilcoxon test data, it was found that consultation for parents was effective to improve students' assertive behavior (Z = -1.826, p = < 0.05). Based on the results, it can be concluded that the implementation of consultation for parents to improve assertive behavior of students has been tested effectively and can be implemented in order to help students deal with problems, especially in low student assertive behavior.